(untitled) (Bangladesh Medical Journal, 2021)
Bony changes in lepromatous leprosy are one of the causes of deformity and disability. Fasting calcium and creatinine ratio in urine is used as a bone resorption marker in a number of diseases such as hyperthyroidism, osteoporosis, multiple myeloma, paget’s disease and sarcodosis. In lepromatous leprosy assessment of bone resorption might be done with that marker. To assess the role of fasting urinary calcium and creatinine ratio as a marker of bone resorption in patients with lepromatous leprosy. A case control study was conducted on 28 patients diagnosed as lepromatous leprosy and 28 age-matched healthy control. The participants who fulfilled all inclusion and exclusion criteria were studied by measuring fasting urinary calcium and creatinine level as well as observing X-rays of both hands and feet of affected individuals. The mean age of cases 38.1±14.2 years and 38.9±12.9 years was in control group. Male - female ratio was 3.6: 1. It was observed that 10.7% leprosy patients showed urinary Ca/Cr ratio >0.20 (0.13±0.12) and 10.7% healthy control showed urinary Ca/Cr ratio ratio>0.20 (mean ±SD 0.11±0.7). the difference was not statistically significant (p>0.05). X-ray finding was positive in 14.3% leprosy patients and none of the control group. That difference was not significant statistically (p>0.05). there was no relation between raised urinary Ca/Cr ratio and positive findings of bone resorption on x-rays among the leprosy cases. Bangladesh Med J. 2019 Sep; 48 (3): 28-33